Microwave Absorption in Ge After Bombardment of Helium Ions Beam - Serhii Lysochenko; Oleg Kukharenko; Volodymyr Ilchenko; Mykola Tolmachov; Viktor Oliynyk; Vilen Launets; Volodymyr Zagorodnii (Advanced Physics Research, 2024)
Abstract In this work, the effect of Ge sample bombardment by energy Ei = 1.2 MeV mono‐energetic He+ ions within the fluence range of 1013–1.2 × 1015 cm−2 on the microwave reflection/transmission modification in the frequency range of 26–38 GHz is investigated. It is shown for the first time that such Ge treatment allows achieving a drastic increase in its interaction with microwaves. After the 1 µm thick undersurface area of Ge, accounting for less than 10−3 of its bulk, underwent the fluence of 1.2 × 1015 cm−2, the increase of the microwave absorption coefficient from 0.06 to 0.78 and decrease of the microwave reflection coefficient from 0.7 to 0.18 are observed. This is caused by the occurrence of dangling atomic bonds in nanoscale cavities inside the material. Most probable energy loss mechanisms of microwaves in modified Ge are suggested. Modified semiconductor structures can be used as microwave‐absorbing coverings, devices employing a periodic structure of materials or a gradient of its properties.